Pendidikan Perempuan di Minangkabau pada Era Politik Etis (1901-1942) - Nisa Ulaini; Sri Handayani; Fitra Rahmadani; Dzikril Jipa; Zikra Karmila (Tarikhuna: Journal of History and History Education, 2023)
Ethical politics carried out by the Dutch colonial government towards the Minangkabau community provided great opportunities for the advancement of Minangkabau education. One of the striking Dutch policies was its education, and this education policy became the core of this colonial policy. Therefore, at the beginning of the 20th century in Minangkabau, there was a movement carried out by several women, one of which was Rahmah El Yunus. This research is a literature study that uses a philosophical approach and a historical approach. The data analysis techniques used in this study are descriptive analysis techniques and content analysis. From the results of this research on Women's Education in Minangkabau in the Era of Ethical Politics, there is a girls' school in Minangkabau, namely Diniyyah Puteri Padang Panjang founded by Rahmah El Yunus. Rahmah El Yunus was very motivated to make Minangkabau women more advanced and intelligent by establishing a special school for girls, namely the Diniyyah Putri Padang Panjang school. The importance of education is not only for men, but also for women. A woman who gets an education will be an example for her child and also her family.